Evaluation of the prevalence of comorbidities in patients reporting for dentoalveolar surgeries - Srivalli Natarajan; Taher Abbas Mistry; Usha Asnani (Wolters Kluwer Medknow Publications, 2019)
Background: Medical comorbidities have varied effects on the management of a patient for dentoalveolar surgeries. Prior diagnosis and prudence in such conditions is of utmost importance for avoidance of complications and overall welfare of the patient. There is a dilemma on the extent of investigations required to evidently ascertain the medical status and fitness of a patient for a dental procedure. The objective of this study was to evaluate the prevalence of medical comorbidities in patients reporting for dentoalveolar surgeries, which would help provide data to establish an evidence-based protocol for perioperative workup of all dental surgeries. Methodology: A total of 2872 patients were included in this study age ranging from 13 years to 84 years. Detailed case history of the patient and baseline blood investigations were recorded. Physician's consultation was acquired to identify any medical comorbidity the patient may be suffering from. Results: It was observed that 17.8% of the patients were detected with medical co-morbidities. Hypertension and Diabetes being the most prevalent (Hypertension: 9.1% and Diabetes: 6.2%). This study has shown that 8.8% of all patients in our study were either newly diagnosed with comorbidities or were inappropriately treated for a prediagnosed comorbidity. Conclusion: We conclude that only relying on the medical history provided by the patient is not sufficient to rule out any medical comorbidities and there is a chance of missing out on any undiagnosed medical condition that the patient may be suffering from.